Principles of Islamic Education Management - Mawan Rinaldi Silalahi*; Miftah Royyani Fahmi; Awaluddin Siregar (Universitas Syiah Kuala, 2023)
Planning, organizing, directing, and evaluating are part of Islamic education management, which is the process of managing Islamic educational resources effectively and efficiently to achieve Islamic education goals. with guiding principles and core success-oriented values. The Panca Jiwa principle is the best foundation in managing Islamic education so that students can move in school. Sincerity, Simplicity, Independence, Ukhuwah Islamiyah, and Freedom are the five principles of the five souls, as the name suggests. The Panca Jiwa fills in as the main rule underlying strong Islamic training standards. Qualitative descriptive methods were used in this study. The findings of this study come from a review of the literature. The findings illustrate the principles of Islamic Education Management.